Bridging the Academic-Industry Gap: A Role Play Peer Review Method for Teaching Software Engineering - Bittal, Vijaylaxmi; Alfatmi, Khalid (Journal of Engineering Education Transformations, 2025)
Traditional educational methods of teaching software engineering often stall to align with industry standards. Theoretical instruction, which emphasizes concepts and procedures, does not sufficient to prepare students for real-world applications. Consequently, students struggle to apply their knowledge in practical scenarios. This paper introduces the Role Play Peer Review Learning (RPL) approach to address this gap. In the RPL approach, students are assigned various roles within the software development cycle and engage in peer reviews. This method has been implemented in a classroom setting, and this paper presents the results of its application, demonstrating its effectiveness in bridging the gap between academic instruction and industry-level software engineering practices.